TERRORISM AS A COMMUNICATION PHENOMENON - ATANESIAN, Arthur (CENTRAL ASIA AND THE CAUCASUS, 2009)
Some of the contemporary theories of the mass media and political communications1 teach their audiences and mold public ideas about events or phenomena which political forces exploit for their own ends. The media do not merely cover events or describe phenomena— they cover them with “outgrowths” that disfigure them to the extent that the public gradually shifts from discussing the real phenomenon to its virtual likeness, which might well be a product of media skills. This explains why from time to time the public concentrates on phantoms at the expense of real and even urgent issues, which remain uncovered and therefore ignored The agenda-setting theory postulates: “We judge as important what the media judge as important.”2 Significantly, according to the agenda-setting theory the media determines not merely what the public would think but also the objects of its deliberations: “The press may not be successful much of the time in telling people what to think, but it is stunningly successful in telling its readers what to think about.”3 This is true when applied to the press; the electronic media—TV and the Internet—have gone even further. They not merely suggest what people should think about—they tell them what they should think, how to treat the events, and what terms should be applied.